Implementasi Teknik Ecoprint Sebagai Strategi Peningkatan Kesadaran Lingkungan pada Siswa Sekolah Dasar - Nurpazriah, Mainawati; Firdaus, Muhammad Rihap; Fakhira, Nisrina Lulu; Nurjanah, Tiya (TAFANI: Jurnal Pengabdian Masyarakat, 2025)
The 2024 Community Service Program (KKN) used the Sisdamas model (Community Empowerment-Based Community Service), with the theme "Implementation of Ecoprint Techniques as a Strategy to Increase Environmental Awareness Among Elementary School Students." The author designed several programs to support this theme, including: (1) assessing the community's and students' awareness of utilizing natural materials, (2) enhancing children's creativity in using natural resources, (3) socializing the ecoprint technique to students, and (4) facilitating free ecoprint workshops. This activity aimed to raise environmental awareness among students at SD Negeri Buah Batu through a participatory approach. The program was implemented on August 15, 2024, involving 5th-grade students actively in every phase, from the introduction of the ecoprint concept to hands-on practice using the pounding technique with leaves as the primary material. The results showed an increase in students' understanding and skills in using natural materials to create eco-friendly artistic products while also reinforcing their awareness of environmental preservation. This program proved effective in integrating environmental education values with creative, hands-on practices, encouraging students to care more about the environment through enjoyable and meaningful activities.